Ghana Local Government Procurement: A Path Towards Fairness, Efficiency and Transparency - Awudu, Shaibu; Nugraha, Nugraha; Sari, Maya; Furqon, Chairul; Yuliawati, Ayu Krishna (Universitas Pendidikan Indonesia, 2024)
The development of fashion trends has undergone major changes performance in Ghana's local government procurement, taking into account government regulations, supplier capacity and capability, procurement transparency, and supplier diversity. The ordinary least squares regression technique was employed to statistically evaluate data from procurement stakeholders. Our research demonstrates that transparent tools enhance supplier satisfaction and performance without affecting perceptions of justice. Conversely, strict government procurement regulations significantly improve perceptions of fairness as well as supplier satisfaction and performance. Supplier capacity and capability disparities adversely affect the results, while diversity programs do not significantly impact either outcome. The results indicate that suppliers are more content and perform better when strict restrictions and transparency mechanisms are in place. However, inadequate execution of diversity policies and competence discrepancies undermine fairness and engagement. This research supports the resource-based view theory, which contends that robust procurement regulations are essential for achieving long-term success. Legislators should prioritize capacity-building programs and diversity initiatives to ensure successful and equitable procurement procedures. This research is distinctive in that it surpasses the conventional compartmentalized approach by conducting a comprehensive and concurrent analysis of a multitude of procurement aspects. This comprehensive approach, which illuminates the interplay between numerous factors, has the potential to enhance public procurement policy and strategy.